Mathematical Modeling of The Transmission Dynamics of Monkeypox with the Impact of Quarantine and Public Enlightenment in Nigeria - Onitilo, Sefiu; Ajanı, Abiodun; Danıel, Deborah; Haruna, Ayobami (Bursa Teknik Üniversitesi, 2024)
Monkeypox remains a public health concern in Nigeria, with periodic outbreaks reported. Despite efforts to control the disease, the number of reported cases continues to rise. Understanding the transmission dynamics of monkeypox and predicting its future spread can inform public health decision-making and guide the allocation of resources for control efforts. Hence, in this study, a deterministic model for the transmission dynamics of Monkeypox in the presence of quarantine and public enlightenment is presented. The model analysis involving the Disease Free Equilibrium (DFE) is established. Numerical simulations were used to better investigate the impact of quarantine and public enlightenment on human population. The results revealed that the effectiveness of the combined form of public awareness and quarantine produced more results followed by the effectiveness of public awareness alone, and then the result achieved when infected individuals are quarantined. If the measures were implemented with a greater degree of integration, there would be a significant reduction in the viral peak, thereby preventing its persistence within the human population.
Keywords: Applied Mathematics (Other); Uygulamalı Matematik (Diğer)